Effect of Naftopidil on Bladder Microcirculation in a Rat Model of Bladder Outlet Obstruction. Issue 2 (6th November 2015) - MAJIMA, Tsuyoshi; YAMAMOTO, Tokunori; FUNAHASHI, Yasuhito; TAKAI, Shun; MATSUKAWA, Yoshihisa; YOSHIDA, Masaki; GOTOH, Momokazu
Abstract : Objectives: To evaluate the effect of naftopidil on bladder capillary blood flow using bladder outlet obstruction model rats. Methods: Female Sprague–Dawley rats were divided into three groups: control group, bladder‐outlet‐obstruction group, and bladder‐outlet‐obstruction + naftopidil group. Bladder‐outlet‐obstruction surgery was performed in the bladder‐outlet‐obstruction and bladder‐outlet‐obstruction + naftopidil groups. The control group received sham‐operation. The bladder‐outlet‐obstruction + naftopidil group were treated with naftopidil (30 mg/kg) for 14 days after bladder‐outlet‐obstruction operation, while the control and bladder‐outlet‐obstruction groups were treated with vehicle. Continuous cystometry was performed 14 days after the surgery. Bladder blood flow was measured after 14 days using a pencil lens charge‐coupled device microscopy system. The bladder was then harvested for histology and measuring 8‐hydroxy‐2′‐deoxyguanosine tissue level by enzyme‐linked immunosorbent assay. Results: In cystometry, the bladder‐outlet‐obstruction rats showed bladder overactivity, while naftopidil treatment improved the cystometric pattern. The blood flow through the submucosal capillaries of the bladder base in the bladder‐outlet‐obstruction group was lesser than that in the control, whereas the bladder‐outlet‐obstruction + naftopidil group showed significantly greater blood flow than the bladder‐outlet‐obstruction group. The bladder tissue in the bladder‐outlet‐obstruction group showed a tendency to contain more hypertrophic detrusor muscle and inflammatory cells compared to those in the control group, while naftopidil treatment suppressed these histological changes. The 8‐hydroxy‐2′‐deoxyguanosine levels in the bladder tissue significantly differed among the three groups (the bladder‐outlet‐obstruction group > the bladder‐outlet‐obstruction + naftopidil group > the control group). Conclusions: Naftopidil improved bladder overactivity as well as the impaired bladder blood flow.caused by bladder‐outlet‐obstruction.